The treatment of tendon injury with electromagnetic fields evidenced by advanced ultrasound image processing. (3rd July 2015) - Parker, Richard; Markov, Marko
Abstract: This article presents a novel modality for accelerating the repair of tendon and ligament lesions by means of a specifically designed electromagnetic field in an equine model. This novel therapeutic approach employs a delivery system that induces a specific electrical signal from an external magnetic field derived from Superconductive QUantum Interference Device (SQUID) measurements of injured vs. healthy tissue. Evaluation of this therapy technique is enabled by a proposed new technology described as Predictive Analytical Imagery (PAI™). This technique examines an ultrasound grayscale image and seeks to evaluate it by means of look-ahead predictive algorithms and digital signal processing. The net result is a significant reduction in background noise and the production of a high-resolution grayscale or digital image.